Climate change winners and losers: The effects of climate change on five palm species in the Southeastern United States. Issue 19 (1st September 2020) - Butler, Christopher J.; Larson, Matt
Abstract: Palms (Arecaceae) are a relatively speciose family and provide materials for food, construction, and handicraft, especially in the tropics. They are frequently used as paleo‐indicators for megathermal climates, and therefore, it is logical to predict that palms will benefit from predicted warmer temperatures under anthropogenic climate change. We created species distribution models to explore the projected ranges of five widespread southeastern North American palm species ( Rhapidophyllum hystrix, Sabal etonia, Sabal minor, Sabal palmetto, and Serenoa repens ) under four climate change scenarios through 2070. We project that the amount of habitat with >50% suitability for S. etonia will decline by a median of 50% by 2070, while the amount of habitat with >50% suitability S. minor will decline by a median of 97%. In contrast, the amount of suitable habitat for Rhapidophyllum hystrix will remain stable, while the amount of suitable habitat for Serenoa repens will slightly increase. The projected distribution for S. palmetto will increase substantially, by a median of approximately 21% across all scenarios. The centroid of the range of each species will shift generally north at a median rate of 23.5 km/decade. These five palm species have limited dispersal ability and require a relatively long time to mature and set fruit. Consequently, it is likely that the change in the distribution of these palms will lag behind the projected changes in climate. However, Arecaceae can modify physiological responses to heat and drought, which may permit these palms to persist as local conditions become increasingly inappropriate. Nonetheless, this plasticity is unlikely to indefinitely prevent local extinctions. Abstract : Palms (Arecaceae) are widely used as paleo‐indicators of megathermal climates, and it would be expected that the their range should increase with anthropogenic climate change. We examined the potential effects of climate change by 2070 on five widespread palm species in the southeastern United States and find that the amount of suitable habitat for two species will decline substantially, one species will remain essentially unchanged, and two species will benefit.